THE URGENCY OF REGULATING CASH ON DELIVERY COURIER PROTECTION IN INDONESIA'S E-COMMERCE ECOSYSTEM - Dede Al Mustaqim Mustaqim (Faculty of Law Atma Jaya Yogyakarta University, 2026)
The rapid growth of e-commerce in Indonesia has driven the widespread use of the Cash on Delivery (COD) payment system. However, behind the convenience of such transactions, COD couriers face various risks, ranging from physical violence by consumers and transaction fraud to work-related accidents with minimal protection. This condition highlights a regulatory gap that does not explicitly provide legal protection for couriers, despite their role as the frontliners in the digital ecosystem. The main problems examined in this study are the legal position of COD couriers within Indonesia’s e-commerce ecosystem, the risks they encounter, the extent to which existing regulations provide protection, and the urgency of establishing specific regulations to protect couriers as vulnerable workers. This research employs a normative juridical method with a statute approach and a conceptual approach. Author also conducted interviews with 10 COD couriers and observations from a Facebook community group of couriers. The data were analyzed qualitatively using content analysis. The findings reveal a legal vacuum that leaves COD couriers in the status of vulnerable workers. Current regulations still prioritize consumers and business actors without encompassing the protection of couriers. Therefore, a specific regulation is urgently needed in the form of a Government Regulation or Ministerial Regulation that stipulates the obligations of e-commerce platforms, the responsibilities of logistics companies, social security schemes, and a fast-track dispute resolution mechanism. In conclusion, legal protection for COD couriers is essential to ensure justice, legal certainty, and utility within Indonesia’s e-commerce ecosystem.